MANAGEMENT CULTURE IN STUDENTS DEVELOPMENT METHODS - Hamdamova Makhzuna Tursunovna (Scholars Digest Publishing, 2023)
This article presents opinions on the improvement of the organizational and management mechanisms for the development of management activities of the heads of higher education institutions in resolving conflict situations. The reasons for the origin of conflicts and the pedagogical aspects of their positive resolution, the importance of pedagogues in management activities are given.
Keywords: Education, future, teacher, educator, principles of education, student, young generation, higher education, conflicts, conflict situation.